Association between mental health, caries experience and gingival health of adolescents in sub-urban Nigeria - El Tantawi, Maha (BMC Oral Health, 2021)
BACKGROUND: This study assessed the association of mental health problems and risk indicators of mental health problems with caries experience and moderate/severe gingivitis in adolescents. METHODS: A cross-sectional household survey was conducted in Osun State, Nigeria. Data collected from 10 to 19-years-old adolescents between December 2018 and January 2019 were sociodemographic variables (age, sex, socioeconomic status); oral health indicators (tooth brushing, use of fluoridated toothpaste, consumption of refined carbohydrates in-between-meals, dental services utilization, dental anxiety and plaque); mental health indicators (smoking habits, intake of alcohol and use of psychoactive drugs) and mental health problems (low and high). Gingival health (healthy gingiva/mild gingivitis versus moderate/severe gingivitis) and caries experience (present or absent) were also assessed. A series of five logistic regression models were constructed to determine the association between presence of caries experience and presence of moderate/severe gingivitis) with blocks of independent variables. The blocks were: model 1—sociodemographic factors; model 2—oral health indicators; model 3—mental health indicators and model 4—mental health problems. Model 5 included all factors from models 1 to 4. RESULTS: There were 1234 adolescents with a mean (SD) age of 14.6 (2.7) years. Also, 21.1% of participants had high risk of mental health problems, 3.7% had caries experience, and 8.1% had moderate/severe gingivitis. Model 5 had the best fit for the two dependent variables. The use of psychoactive substances (AOR 2.67; 95% CI 1.14, 6.26) was associated with significantly higher odds of caries experience. The frequent consumption of refined carbohydrates in-between-meals (AOR: 0.41; 95% CI 0.25, 0.66) and severe dental anxiety (AOR0.48; 95% CI 0.23, 0.99) were associated with significantly lower odds of moderate/severe gingivitis. Plaque was associated with significant higher odds of moderate/severe gingivitis (AOR 13.50; 95% CI 8.66, 21.04). High risk of mental health problems was not significantly associated with caries experience (AOR 1.84; 95% CI 0.97, 3.49) or moderate/severe gingivitis (AOR 0.80; 95% CI 0.45, 1.44). CONCLUSION: The association between mental problems and risk indicators with oral diseases in Nigerian adolescents indicates a need for integrated mental and oral health care to improve the wellbeing of adolescents.